2022
DOI: 10.1097/md.0000000000031250
|View full text |Cite
|
Sign up to set email alerts
|

Association between night sleep latency and hypertension: A cross-sectional study

Abstract: Sleep disorders have been shown to increase the risk of hypertension, while the relationship between night sleep latency and hypertension is less well-known. We aimed to investigate the association between night sleep latency and hypertension, as well as related sleep factors by gender in the Chinese population. We conducted a cross-sectional study of the relationship between night sleep latency and hypertension. The sample size included 619 consecutive hospitalized patients (M/F: 302/317, 64.01 ± 12.27 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Subsequently, the analysis of the PSQI sub-components identified sleep latency as the most affected aspect of sleep quality. Sleep latency is an important dimension of sleep health that is independently associated with hypertension ( 38 ) and depressive symptoms ( 39 ). Prolonged sleep latency among university students may be attributable to excessive smartphone use, often at bedtime, very common in this population group ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the analysis of the PSQI sub-components identified sleep latency as the most affected aspect of sleep quality. Sleep latency is an important dimension of sleep health that is independently associated with hypertension ( 38 ) and depressive symptoms ( 39 ). Prolonged sleep latency among university students may be attributable to excessive smartphone use, often at bedtime, very common in this population group ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that middle-aged stroke participants with PSOL are at greater risk of experiencing a severe stroke, and MIP-1β plays a protective role against IS. Over the years, studies have emphasized that high-risk factors for stroke occurrence (39) and increased stroke severity (5,10,40) include sleep difficulties and advanced age. Notably, while stroke has conventionally been linked to older age, recent years have witnessed a substantial decline in the average age of stroke onset, coupled with a rise in stroke incidence and hospitalization rates among middle-aged individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise mechanisms by which PSOL and age impact the development of ischemic stroke (IS) remain incompletely understood. Sleep onset latency (SOL) is the amount of time it takes a person to fall asleep in bed, and represents an important marker for assessing sleep quality (5). PSOL is one of the main manifestations of sleep structural changes in ischemic stroke (6).…”
Section: Introductionmentioning
confidence: 99%
“…Zhong et al 20 have shown that longer night sleep latency is associated with an increased risk of hypertension in both men and women, possibly due to the pathological progression of hypertension along with other sleep-related factors. Based on this data, an increase in the frequency of night shifts within a month could exacerbate the negative effects on arterial blood pressure.…”
Section: Discussionmentioning
confidence: 99%